Electoral violence prevention: what works?. Issue 3 (3rd April 2018) - Birch, Sarah; Muchlinski, David
ABSTRACT: Elections are in theory democratic means of resolving disputes and making collective decisions, yet too often force is employed to distort the electoral process. The post-Cold War increase in the number of electoral authoritarian and hybrid states has brought this problem into relief. In recent years the prevention of electoral violence has played an increasingly large role in the democratic assistance activities undertaken by international agencies, following increased awareness within the international community of the specific security challenges that elections entail. However, there has to date been little systematic evaluation of the success of different electoral violence prevention (EVP) strategies in reforming electoral institutions so as to enable them to maintain the peace during the electoral period. This article assesses the effectiveness of two common types of international EVP activity. Using a new global dataset of EVP strategies between 2003 and 2015, this article finds evidence that capacity-building strategies reduce violence by non-state actors, whereas attitude-transforming strategies are associated with a reduction in violence by state actors and their allies. The findings are relevant both for understanding the dynamics of electoral violence, and also for policymakers and electoral assistance providers in the international community who have responsibility for the design of democratic assistance projects in states at risk of electoral violence.